Benefit of Targeting a LDL (Low-Density Lipoprotein) Cholesterol <70 mg/dL During 5 Years After Ischemic Stroke. Issue 4 (April 2020) - Amarenco, Pierre; Kim, Jong S.; Labreuche, Julien; Charles, Hugo; Giroud, Maurice; Lee, Byung-Chul; Mahagne, Marie-Hélène; Nighoghossian, Norbert; Gabriel Steg, Philippe; Vicaut, Éric; Bruckert, Eric; Touboul, Pierre-Jean; et al.
Abstract : Background and Purpose—: The TST trial (Treat Stroke to Target) evaluated the benefit of targeting a LDL (low-density lipoprotein) cholesterol of <70 mg/dL to reduce the risk of cardiovascular events in 2860 patients with ischemic stroke with atherosclerotic stenosis of cerebral vasculature or aortic arch plaque >4 mm, in a French and Korean population. The follow-up lasted a median of 5.3 years in French patients (similar to the median follow-up time in the SPARCL trial [Stroke Prevention by Aggressive Reduction in Cholesterol Level]) and 2.0 years in Korean patients. Exposure duration to statin is a well-known driver for cardiovascular risk reduction. We report here the TST results in the French cohort. Methods—: One thousand seventy-three French patients were assigned to <70 mg/dL (1.8 mmol/L) and 1075 to 100±10 mg/dL (90–110 mg/dL, 2.3–2.8 mmol/L). To achieve these goals, investigators used the statin and dosage of their choice and added ezetimibe on top if needed. The primary outcome was the composite of ischemic stroke, myocardial infarction, new symptoms requiring urgent coronary or carotid revascularization and vascular death. Results—: After a median follow-up of 5.3 years, the achieved LDL cholesterol was 66 (1.69 mmol/L) and 96 mg/dL (2.46 mmol/L) on average, respectively. The primary end point occurred in 9.6% and 12.9% of patients, respectively (HR, 0.74 [95% CI, 0.57–0.94]; P =0.019). Cerebral infarction or urgent carotid revascularization following transient ischemic attack was reduced by 27% ( P =0.046). Cerebral infarction or intracranial hemorrhage was reduced by 28% ( P =0.023). The primary outcome or intracranial hemorrhage was reduced by 25% ( P =0.021). Intracranial hemorrhages occurred in 13 and 11 patients, respectively (HR, 1.17 [95% CI, 0.53–2.62]; P =0.70). Conclusions—: After an ischemic stroke of documented atherosclerotic origin, targeting a LDL cholesterol of <70 mg/dL during 5.3 years avoided 1 subsequent major vascular event in 4 (number needed to treat of 30) and no increase in intracranial hemorrhage. Registration—: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01252875. Abstract : Supplemental Digital Content is available in the text.